The Analysis of the Cinema Language via decoding technical codes of the Kurdish Film “Crossing the Dust” - Ahmed, Shorashvan; Moussa, Abdelwahab (Humanities Journal of University of Zakho, 2022)
The Social nature of human beings make them search for many means of communication and expression whether linguistically or non-linguistically. One of the means that is used for this purpose is cinema. Cinema plays an important role in the life of human beings whether through the contents it presents or the great influence on the receiver it has because it reflects the social value in culture and the styles of life. It deals with the needs of people, their basic issues, their wishes, goals and dreams. It also attempts to help emotionally, intellectually and culturally, etc. This popular means has become a magic window and through which we can see ourselves and the surrounding external world. Additionally, Kurds, through cinema, could express many of their issues concerned with the Kurdish people in general and individuals in particular through all the tragic events they experienced. The present study aims at analyzing cinema language via decoding technical codes of the Kurdish film “Crossing the Dust”. The special language of cinema depends on many codes including technical codes. In each film, many technical codes are used to state their meanings and purpose of their uses. To conduct this research, the film “Crossing the Dust” has been utilized and analyzed semiologically according to John Fisk’s model. After specifying the technical codes in the scenes, they are analyzed according to their meanings, purposes and functions.